THE EFFECT OF STRESS AND DISCIPLINE ON EMPLOYEE ACHIEVEMENT IN THE BANK OF DANAMON SOUTH TANGERANG - Sutoro, Moh (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
Companies always have problems with employee performance. However, sometimes factors from the individual side are difficult to know, such as stress and work discipline. This research, trying to analyze and describe the phenomena that occur in Bank Danamon employees. The quantitative approach was chosen because it has advantages, therefore the analysis method uses multiple linear regression. The number of samples is 60 employees and the sampling technique used is census. The research instrument uses a questionnaire spread method with a closed statement form. The results showed work stress has a significant effect on work performance of 0,436. Work discipline has a significant effect on work performance of 0,400. Jointly work stress and work discipline have a significant effect on work performance with a determination coefficient of 0,252